Histomorphological Study on the Neurohypophysis of Jaffarabadi Buffalo during Different Seasons - Anil Sharma; Vyas, Y. L.; Vishnudeo Kumar; Singh, Vivek Kumar (Indian Journal of Veterinary Anatomy, 2026)
The study was conducted on neurohypophysis of 30 adult Jaffarabadi buffaloes to explore the histomorphological changes during different seasons. The tissue samples were collected during the winter, summer and rainy seasons (10 samples during each season) from the slaughterhouse. The samples were processed and stained with various histological stains, by standard procedures. The pars nervosa and infundibulum were two main components of the neurohypophysis, which forms the caudo-dorsal portion of the pituitary gland. Both parts consisted of axon bundles and pituicytes (cells of neurohypophysis). The neurosecretory material was distributed diffusely along with the axonal bundles and blood vessels. In addition to diffuse neurosecretory material, membrane-bound, round or oval-shaped accumulations (Herring body) were also observed between the axonal bundles and close to the blood vessels. During winter the average diameter of the Herring body was smallest which increased gradually during summer and the rainy season. The diameters of Herring bodies were significantly higher during the rainy season. The pituicytes showed a wide variation in the shape and size of cells and nuclei. The highest cell density was observed during the summer season as compared to the winter and rainy seasons.